Teaching Design in Adolescent Environments: Twinning Secondary and Tertiary Learning Experiences - David Jones (Landscape Review, 2004)
Increasingly our landscape architecture teaching and educational pedagogies are facing an internationalisation in approach and expectation. We are positioned within a tertiary learning layer in a tripartite educational system for which each layer assumes certain expectations and outcomes. But their vertical linkages are unclear, and we incorrectly assume continuity of knowledge and skill learning strategies. It is a horizontally stratified teaching setting that we have to work within and while we can think of internationalisation as occurring within our level we need to appreciate that internationalisation is also occurring at the secondary level. This paper discusses the educational environment within which globalisation is occurring, and reviews a project model that builds bridges vertically between secondary and tertiary learning environments. The project displays possibilities in both secondary and tertiary educational sectors, but especially in enhancing and improving the design fluency of our annual incoming cohorts who often possess a naive understanding of built environmental design. Commencing in 1998 as an experimental project, it has been recognised at the South Australian state level as a forward-thinking initiative that has radically transformed secondary school Design teacher's perspectives as to educational possibilities, and substantially matured attitudes to landscape design by both suites of participants. As a consequence, it is an educational project that has experienced requests from numerous secondary schools around the State to participate.